{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Week 7 notes

# Week 7 notes - To solve a system of two equations in two...

This preview shows pages 1–5. Sign up to view the full content.

To solve a system of two equations in two variables, find all ordered pairs, if any, which are solutions of both equations. **The graph of a linear equation in two variables is a straight line.** When a line intersects the y-axis what is the value of x?= 0 A system of equations is consistent if it has at least one solution. If it has no solution it is inconsistent. The equations are dependent if the system has infinitely many solutions. If it has exactly one solution or no solution it is independent. Solve the system of equations by graphing. Then classify the system X+y=15 x-y= 1 x+y=15 if x=6 then 6+y=15 Y=9 (6,9) X+y=15 If y=5 then X+5=15 X=10 (10,5) x-y=1 if x =0 then 0-y=1 Y=-1 (0,-1) x-y=1 y=0 then x-0=1 x=-1 (1,0) The solution of the system is: (8,7) The system is consistent The equations are independent Solve the system of equations by graphing. Then classify the system. 2x-y=18 2x+3y=2 2x-y=18 If x=8 then 16-y=18 Y=-2 (8,-2) 2x-y=18 If y=-6 then 2x-(-6)=18 X=6 (6,-6) 2x+3y=2 If X=0 then 3y=2 Y= 2/3 =.66 (0,2/3) 2x+3y=2 If Y=0 then 2x=2 X=1 (1,0)

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
The solution is (7,-4) The system is consistent The equations are independent Solve the system of equations by graphing. Then classify the system 6u+v=11 6u=v+25 (U= x, V=y) 6u+v=11 If U = 1 then 6+v=11 V= 5 (1,5) 6u+v=11 If V=-1 then 6u=-1=11 U=2 (2,-1) 6U=V+25 If U=0 then V+25 -25=V (0,-25) 6U=V+25 If V=0 then 6U=25 (25,0) The solution is (3,-7) The system is consistent The equations are independent Solve the system of equations by graphing. Then classify the system Y= -x-9 4x-3y= -15 Y= -x-9 If Y=-2 then -2= -x-9 X= -9+2 X= -7 (-7,2) Y= -x-9 If X=4 then Y= -4-9 Y= -13 (4,-13) 4x-3y=15 If X=0 then -3y=15 Y= -5 (0,-5) 4x-3y=15 If Y=0 then 4x=15 X= 15/4= 3.75 (3.75,0) The solution is (-6,-3) The system is consistent The equations are independentSolve by the SUBSTITUTION method
6x-8y= -12 3x+24=y The 1 st step is to solve an equation for one variable. If the coefficient of a variable is 1 or -1, it is easier to solve for that variable. The 2 nd equation is already solved for y so it is easiest to use. Next, substitute (3x+24) for y into the other original equation. Remember to use parentheses when you substitute. Then remove them carefully. Substitute (3x+24) for y 6x-8(3x+24) = -12 Use the distributive law 6x-24x-192= -12 Collect like terms-18x=180 Finally, solve for x X= -10 Now return to the equations in the problem statement, Substitute for x in either equation to solve for y. Since the second equation is already solved for y it will be easier to use. Substitute -10 for x in the second equation and simply Y= -6 Solve by the SUBSTITUTION Method 3x-9y= -6 7x+74=y 3x-9(7x+74)=-6 3x-63x- 666= -6 -60x= 660 X= -11 7(-11)+74= Y -77+74=Y Y= -3 The solution of the system is (-11,-3) Solve by the SUBSTITUTION Method 9x-2y= -80 8x+75=y

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
9x-2(8x+75)= -80 9x-16x-150= -80 -7x=70 X= -10 8(-10)+75=y -80+75=Y -5=y The solution to the system is (-10,-5) Solve by the SUBSTITUTION method 5m+n=4 m-9n=10 **If the coefficient of a variable is 1 or -1, then it is easier to solve for that variable**
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 15

Week 7 notes - To solve a system of two equations in two...

This preview shows document pages 1 - 5. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online